Recent Progress and Prospects on Metal Halide Perovskite Nanocrystals as Color Converters in the Fabrication of White Light-Emitting Diodes - Mohapatra, Ashutosh; Kar, Manav R.; Bhaumik, Saikat (Frontiers in Electronic Materials, 2022)
Recently, metal halide perovskite nanocrystals (NCs) have shown significant progress and have attracted great interest in a wide range of applications, such as solar cells, light-emitting diodes (LEDs), and lasers, photodetectors due to their attractive properties, such as superior PL emission, a wider range of color tunability, narrow emission spectra, better color purity, low cost, easy solution-processability, and so on. In the past, many color converting materials, such as III-nitrides, organics, polymers, metal chalcogenides, were investigated for solid-state lighting (SSL) white light-emitting diodes (WLEDs). Still, they suffer from issues like low stability, low color rendering index (CRI), high correlated color temperature (CCT), low luminous efficiency (LE), and high cost. In this sense, metal halide perovskite NCs exhibit a better color gamut compared to conventional lighting sources, and production costs are comparatively cheaper. Such materials may offer a promising alternative to future color converting WLEDs. In this study, we discuss the metal halide perovskite NCs and their synthesis protocols. Then we elaborate on the recent progress of halide perovskite NCs as a conversion layer in the application of WLEDs.